Analysis of Students' Mathematical Communication Ability in Completing Mathematical Modeling - M Khusnudin; Haninda Bharata (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2022)
Mathematical communication skills are essential skills that students must have in learning mathematics. The communication process can help students build their understanding of concepts in mathematics and are easy to understand. Mathematical communication is a tool for transmitting mathematical knowledge in building mathematical knowledge in learning activities. Indicators of students' ability to communicate mathematically in learning mathematics are (1) expressing mathematical ideas by speaking, writing, demonstrating, and describing them in visual form, (2) understanding, interpreting, and assessing mathematical ideas presented in written, oral or visual form, (3) use language, notation and mathematical structure to express ideas, draw relationships and build models. This study aims to: (1) describe the mathematical communication skills of grade 7 students in completing mathematical modeling on the One Variable Linear Equation (PLSV) material and (2) identify the components of students' mathematical communication skills on each achievement indicator. This research is a qualitative descriptive study. A qualitative approach is used to understand the context of the subject. Based on the three indicators of students' mathematical communication skills, an average of 17.86% of students' skills can be classified as very low. It shows that most students cannot model solving real problems or everyday life related to mathematical communication.